Utilization of Local Cassava Plants to Make Tape as an Effort to Empower MSMEs in Mainan Village - Fitriah; S, Adam Gheral; Attiahilla , Ranaya; Putri, Nindi Savira; Alie , Juhaini; Munandar, Aris; Ghina, Aliah (Manunggal Halim Jaya, 2025)
This study analyzes the utilization of local cassava plants through processing them into tape as a strategy for empowering MSMEs in Mainan Village. The research method used a qualitative approach with literature studies and field observations to examine the production process, economic contribution, and challenges faced. The results show that processing cassava into tape provides significant added value through increased income, job creation, and strengthening the village's economic identity. Furthermore, product innovation and business mentoring have proven to be strategic factors in increasing the competitiveness of tape MSMEs. However, limited capital, the need for halal certification, and product quality standards remain major obstacles that must be overcome. Therefore, multi-stakeholder collaboration based on the Pentahelix model is considered essential to encourage the development of tape MSMEs as an example of sustainable local economic empowerment practices.